Strategi Komunikasi Branding Festival Olahraga Rekreasi Nasional Viii 2025 Sebagai Promosi Sport Tourism Nusa Tenggara Barat - Hasbullah, S.ST.; Swandi, I Wayan; Artayasa, Artayasa (UHN IGB Sugriwa Denpasar, 2026)
The organization of the 8th National Recreational Sports Festival (FORNAS) in 2025 will be a strategic momentum for West Nusa Tenggara (NTB) Province to solidify its position as a premier sports tourism destination. The main challenge in communicating this branding event is to change public perception of recreational sports so that they have the same prestige and tourist appeal as competitive sports. This research aims to analyze the branding communication strategies implemented in building the identity and positive image of FORNAS VIII 2025. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through in-depth interviews with key stakeholders (KORMI NTB and the Tourism Office), observation of visual elements and communication media, and document studies. The conceptual basis of this research refers to branding strategy theory, which includes formulating brand identity, brand positioning, and brand communication. The research results indicate that the branding communication strategy for FORNAS VIII 2025 is centered on the concept of Cultural and Fitness Synergy. This strategy is implemented thru three main tactics: (1) Identity Visualization: Using local textile elements and NTB's endemic fauna in the logo and mascot to create strong visual differentiation; (2) Symbolic Narrative: Building the message that recreational sports are part of a lifestyle and cultural preservation, not just competition; and (3) Digital Activation: Utilizing social media to build engagement thru content that highlights the exoticism of NTB's tourist destinations. In conclusion, the branding communication carried out not only serves as a promotion for the event but also as an effective city branding tool for NTB post-pandemics, although it still requires consistency in messaging across various media lines.